2009
DOI: 10.1021/ef9007592
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Study of Polar Species in Untreated and Hydrotreated Gas Oil Samples by Electrospray Ionization Fourier Transform Ion Cyclotron Resonance Mass Spectrometry (ESI FTICR−MS)

Abstract: Two gas oil samples, untreated feed and hydrotreated product oil, were analyzed. Both basic and acidic polar species were detected by electrospray ionization (ESI) Fourier transform ion cyclotron resonance mass spectrometry, and the detected species were characterized on the basis of their elemental compositions. Samples were real refinery samples, with one sample being a certain distillation fraction of crude oil (feed) and the other sample being a hydrotreated feed oil (product). Comparison of the compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
5
18
0
Order By: Relevance
“…Only the N2 class remains fairly resistant to hydrotreatment 40 . Liu et al 34 and Zhang et al 41 showed that N 1 class species in atmospheric residue and deasphalted oil, respectively, were more easily hydrogenated when they had high aromaticity and/or low carbon number.…”
mentioning
confidence: 99%
“…Only the N2 class remains fairly resistant to hydrotreatment 40 . Liu et al 34 and Zhang et al 41 showed that N 1 class species in atmospheric residue and deasphalted oil, respectively, were more easily hydrogenated when they had high aromaticity and/or low carbon number.…”
mentioning
confidence: 99%
“…While (−)ESI selectively ionizes polar heteroatomic species, (+)APPI is capable of a better ionization of nonpolar compounds. 21,47 The color-coded DBE vs carbon number plot corresponding to the oxygenates present in bio-oil (see Figure S1 Properties of Catalysts. The properties of the fresh ACPbased catalysts and the calcined HZSM-5 zeolite are summarized in Table 2.…”
Section: ■ Resultsmentioning
confidence: 99%
“…These results reveal the different selectivity of both ionization methods towards different component groups. While (-)ESI selectively ionizes polar heteroatomic species, (+)APPI is capable of a better ionization of nonpolar compounds 21,47. The color-coded DBE vs. carbon number plot corresponding to the oxygenates present in bio-oil (see FigureS1…”
mentioning
confidence: 99%
“…Because high‐resolution mass spectrometry is very useful to analyze the crude oil samples, the combination of high‐resolution mass spectrometry with H/D‐exchange emerged as an analytical technique that can be helpful to provide structural information on individual compound. In the previous work, the speciation of nitrogenous compounds in crude oil sample by APCI HDX in combination with high resolution MS was reported .…”
Section: Use Of the In‐apci/appi Source Isotope Exchangementioning
confidence: 99%
“…Recently, the combination of atmospheric pressure ionization techniques have witnessed the development of high-resolution mass spectrometry for structural identification of compounds. 294,[306][307][308][309] Because high-resolution mass spectrometry is very useful to analyze the crude oil samples, 296,[310][311][312][313][314][315][316] the combination of highresolution mass spectrometry with H/D-exchange emerged as an analytical technique that can be helpful to provide structural information on individual compound. In the previous work, the speciation of nitrogenous compounds in crude oil sample by APCI HDX in combination with high resolution MS was reported.…”
Section: Development Software To Process Hdx-ms Datamentioning
confidence: 99%